2019
DOI: 10.1155/2019/7583760
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activity by NKCC1 and Slc26a6 Mediates Acidic pH and Cl Movement after Cardioplegia-Induced Arrest of db/db Diabetic Heart

Abstract: Diabetic heart dysfunctions during cardiac surgeries have revealed several clinical problems associated with ion imbalance. However, the mechanism of ion imbalance mediated by cardioplegia and a diabetic heart is largely unclear. We hypothesized that ion transporters might be regulated differently in the diabetic heart and that the differentially regulated ion transporters may involve in ion imbalance of the diabetic heart after cardioplegic arrest. In this study, we modified the Langendorff-free cardioplegia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…This method uses TI + as a surrogate of K + and a TI + sensitive fluorescent dye (FlixORTM) to visualize TI + uptake through channels in single cells. The Delpire group reported similar results between 86 Rb + and FluxOR [115]. Other techniques include the ammonium pulse technique which uses cardiac strips to measure acidification rate [116].…”
Section: Box 1 Measuring Kcc3 and Nkcc1 Activity Ion-transport Activitymentioning
confidence: 93%
See 1 more Smart Citation
“…This method uses TI + as a surrogate of K + and a TI + sensitive fluorescent dye (FlixORTM) to visualize TI + uptake through channels in single cells. The Delpire group reported similar results between 86 Rb + and FluxOR [115]. Other techniques include the ammonium pulse technique which uses cardiac strips to measure acidification rate [116].…”
Section: Box 1 Measuring Kcc3 and Nkcc1 Activity Ion-transport Activitymentioning
confidence: 93%
“…These findings further emphasizes NKCC1 methylation or histone modification as a potential biomarker in the diagnosis and management of hypertension. More recently, studies by Ji [86] and Andersen [87] et al found increased NKCC activity after cardioplegia induced arrest of diabetic hearts (n=5, P<0.001) and in post infarction heart failure (n=6-7) respectively. These findings indicate the potential role of NKCC in protection of the diabetic heart after cardioplegia infusions and remodelling after myocardial infarction.…”
Section: Nkcc In Vascular Cellsmentioning
confidence: 94%
“…Although the regulation mechanism of various ion transporters is complicated ( 19 ), studies have demonstrated that the expression of SLC26A6 and Cl − transporting activity are upregulated in the type 2 diabetic heart model, which reveals that effective SLC26A6 blockers may be efficient in regulating pH of type 2 diabetic hearts ( 122 ). Additionally, Cl − influx and efflux mediated by SLC26A6 may be beneficial to intracellular acidification in diabetic myocardium during cardioplegia-induced arrest ( 122 ). Evidences reveal that protein kinase C (PKC) can inhibit the transport activity of SLC26A6 ( 19 , 123 ).…”
Section: Slc26a6 and The Heartmentioning
confidence: 99%
“…In addition to cations such as H + and Ca 2+ , the HCO 3 − anion also plays an important role in heart tissues that express HCO 3 − transporters such as the Cl − /HCO 3 − exchanger SLC26A6, which is involved in HCO 3 − influx and efflux [5,64]. SLC26A6 is a Cl − /HCO 3 − exchanger and is mainly expressed in the kidneys and exocrine glands [65][66][67].…”
Section: Bicarbonate Transporters and Their Associated Enzymesmentioning
confidence: 99%